A tale of shells and claws: the signal crayfish as a threat to the pearl mussel Margaritifera margaritifera in Europe - Sousa, Ronaldo Gomes (2019)
The freshwater pearl mussel Margaritifera margaritifera is a highly threatened species in Europe. Several mechanisms may be responsible for the decline in distribution and abundance of European pearl mussel populations, but almost no quantitative data exists about the possible negative impacts of invasive alien species (IAS). In this study, we clearly demonstrate that the invasive signal crayfish Pacifastacus leniusculus predates pearl mussels, using a laboratorial experiment followed by in situ validation in four rivers in the North of Portugal (Mente, Rabacal, Tuela and Baceiro Rivers; Douro Basin). In the laboratory, the crayfish had a clear preference for small-sized pearl mussels but no differences in predation were found in mesocosms with and without sediment. In addition, we clearly demonstrated that the signal crayfish predates pearl mussels in natural conditions and detected a significant density dependent effect (i.e., sites with more crayfish presented higher number of pearl mussel shells with marks of predation). Given the recent introduction of the signal crayfish and the potential negative impacts on pearl mussel populations we also investigated its autoecology (distribution, abundance, size structure and sex-ratio) in the four studied rivers. Significant differences in average abundance and size of the crayfish were detected between sites and the sex-ratio was highly skewed to females. In view of the widespread distribution of signal crayfish (and other invasive crayfish species) in Europe, future management actions devoted to the conservation of pearl mussels should take in consideration the possible negative effects of these predators, especially on juveniles.